Digital Image Watermarking Software Using Discrete Wavelet Transform (DWT) - Zara Marzani (Institute of Information Technology and Social Science (IITSS), 2023)
The ease of data transmission through various digital media poses significant risks to copyright and privacy, often leading to falsification, duplication, fraud, and media piracy. One approach to address this issue is through steganography, a technique for embedding hidden messages within digital documents such as images. A specific application of steganography is Digital Watermarking, which conceals ownership information within digital media. This study employs the Discrete Wavelet Transform (DWT) method to implement watermarking on digital images. DWT divides data into multiple frequency segments that can be independently processed and recombined to form a watermarked image. By embedding a watermark into the image, the proposed method effectively protects against unauthorized use and reproduction.